Media development board game to increase student motivation in studying regional culture - Khusnul Khotimah; Neni Wahyuningtyas (Universitas Negeri Yogyakarta, 2023)
Media development as an effort to introduce regional culture is considered essential to do. Technological developments make students' motivation to study culture begin to fade and shift with the emergence of Western civilization. This is motivated by the need for more interesting local culture introduction media for students and regional, cultural, and educational content in online or offline media. Therefore, learning media is needed to introduce regional culture. The objectives of this development research are: (1) Producing culture game education media board game products; (2) Testing and knowing the feasibility of culture game education media board game products; and (3) Knowing the effectiveness of culture game education board game media products in increasing learning motivation on material Sub Theme 2: